Subcutaneous rituximab in patients with diffuse large B cell lymphoma and follicular lymphoma: Final results of the non‐interventional study MabSCale - Jan Dürig; Jens Uhlig; Anke Gerhardt; Markus Ritter; Gunnar Hapke; Jörg Heßling; Peter Staib; Frieder Wolff; Katja Krumm; Ludwig Fischer vonWeikersthal (Cancer Medicine)
Abstract Background Rituximab has become a standard treatment for non‐Hodgkin lymphoma. Clinical studies have demonstrated the efficacy of rituximab in combination with standard chemotherapies in the treatment of follicular lymphoma (FL) and diffuse large B cell lymphoma (DLBCL) patients. This non‐interventional study aimed to evaluate the effectiveness and safety of subcutaneous (SC) rituximab in routine clinical practice. Methods Adult patients with previously untreated CD20 positive DLBCL or FL who received rituximab SC and chemotherapy as first‐line treatment were observed between 07/2014 and 07/2019 at 99 institutions in Germany. Primary endpoint was the (unconfirmed) complete remission (CR/CRu) rate. Primary outcome was analyzed inferentially; other variables were evaluated descriptively. Results Overall 583 patients (247 FL; 336 DLBCL) were evaluated. CR/CRu rates were 51.4% (95% CI: 45.2; 57.6) in the FL set and 48.5% (95% CI: 43.2; 53.8) in the DLBCL set. Regarding progression‐free survival in the FL group, the probability of being event‐free was 94.2% in the first year and 86.2% in the second year. An overall response was achieved in 85.8% (FL) and 85.4% patients (DLBCL). Patient satisfaction at the end of study with the time saving simplification of the SC vs. intravenous route was 98% for FL and 97% for DLBCL. 45.3% of FL and 47.0% of DLBCL patients experienced an adverse event of grade ≥3. Serious adverse events of grade ≥3 occurred in 27.9% FL and 32.4% DLBCL patients, with the highest incidences for leucopenia, anemia, nausea, and fatigue. No new safety signals were detected. Conclusions The results confirmed the effectiveness and safety of rituximab SC in both the FL and the DLBCL group. Satisfaction of patients and nurses with SC administration was high.